Generation of novel Id2 and E2-2, E2A and HEB antibodies reveals novel Id2 binding partners and species-specific expression of E-proteins in NK cells. (November 2019) - Rautela, Jai; Dagley, Laura F.; Kratina, Tobias; Anthony, Angaleena; Goh, Wilford; Surgenor, Elliot; Delconte, Rebecca B.; Webb, Andrew I.; Elwood, Ngaire; Groom, Joanna R.; Souza-Fonseca-Guimaraes, Fernando; Corcoran, Lynn; et al.
Abstract: NK cells are cytotoxic lymphocytes with a key role in limiting tumour metastases. In mice, the NK cell lineage continually expresses high levels of the Inhibitor of DNA-binding 2 (Id2) protein and loss of Id2 is incongruous with their survival due to aberrant E-protein target gene activity. Using novel Id2 and E-protein antibodies that detect both mouse and human proteins, we have extensively characterised Id2 and E-protein expression in murine and human NK cells. We detected clear expression of E2 A and HEB, and to a lesser extent E2-2 in murine NK cells. In contrast HEB appears to be the major E-protein expressed in human NK cells, with minor E2-2 expression and surprisingly, no E2 A detected in primary NK cells nor human NK cell lines. These novel antibodies are also functional in immunofluorescence and immunoprecipitation. Mass spectrometry analysis of Id2 immuno-precipitated from murine NK cells revealed a number of novel associated proteins including several members of the SWI/SNF-related matrix-associated actin-dependent regulator chromatin (SMARC) and Mediator complex (MED) families. Taken together, these data highlight the utility of novel Id2 and E-protein antibodies and caution against mouse models for understanding Id2/E-protein biology in NK cells given their clearly disparate expression patternbetween species.